Impact of the COVID-19 Pandemic on the Diagnosis and Surgery of Breast Cancer: A Multi-Institutional Study - Kang, Young-Joon; Baek, Jong Min; Kim, Yong-Seok; Jeon, Ye Won; Yoo, Tae-Kyung; Rhu, Jiyoung; Shin, Chang-Hyun; Cho, Shijin; Choi, Hoon; Oh, Se Jeong (Journal of breast cancer, 2021)
The coronavirus disease 2019 (COVID-19) pandemic has significantly impacted the rates of screening, case identification, and referral for cancer diagnosis. We investigated the diagnosis and surgery status of breast cancer before and after the COVID-19 pandemic at a multi-institutional level. We collected breast cancer data from the clinical data warehouse which contained the medical records of patients from six academic institutions in South Korea. Patients were divided into two groups: February to April (period A) and May to July (period B). The data from the two groups were then compared against the same periods in 2019 and 2020. The primary objective was to investigate the differences in breast cancer stages before and after the COVID-19 pandemic. Among 3,038 patients, there was a 9.9% reduction in the number of diagnoses in 2020. This decrease was more significant during period A than period B. The breast cancer stage was not statistically different in period A ( = 0.115), but it was in period B ( = 0.001). In the subset analysis according to age, there was a statistical difference between 2019 and 2020 in period B for patients under the age of 65 years ( = 0.002), but no difference was observed in the other groups. The number of breast cancer cases declined during the pandemic, and the staging distribution has changed after the pandemic peak.